Pengaruh public relation dan strategi periklanan terhadap keputusan pembelian - Sari, Desi Novita; Noorlitaria, Gusti; Asnawati, Asnawati (Faculty of Economics and Business Mulawarman University, 2018)
AbstractThis study aimed to find out : (1) influence of public relation to purchasing decision at Politeknik Negeri Samarinda students, (2) influence of advertising strategy to purchasing decision at Politeknik Negeri Samarinda students, (3) influence of public relation and advertising strategy to purchasing decision at Politeknik Negeri Samarinda Students. This research is a survey research. The population of this research is Politeknik Negeri Samarinda students using Samsung Galaxy mobile phone product. The sampling method used in this research is accidental sampling with 120 respondents. The collected questionnaire data has been tested using validity and reliability. The data analysis technique of this research is multiple linear regression.The results showed that : (1) the public relation positively effected purchasing decisions with a significance value of t-test is smaller than the specified level of significance (2) the advertising strategy positively effected purchasing decisions with significant value t-test is smaller than the specified level of significance (3) the public relation and advertising stategy together positively effected purchasing decisions with significant value f-test is smaller than the specified level of significance.Keywords : Public Relation, Advertising Strategy, Purchase Decision.